2003
DOI: 10.1073/pnas.2237046100
|View full text |Cite
|
Sign up to set email alerts
|

Randomly inserted and targeted Hox/ reporter fusions transcriptionally silenced in Polycomb mutants

Abstract: Polycomb-group (Pc-G) proteins ensure late maintenance of transcriptional repression outside the expression domain of target genes in flies and vertebrates. They act in complexes, presumably by modulating chromatin structure. In Drosophila, they have been found to be associated with transcriptionally inactive loci but seem to be present in association with actively transcribed promoters as well, a feature which is not yet understood. In the mouse, mutations in several Pc-G genes result in an often subtle, loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
4
14
0
Order By: Relevance
“…Therefore, Phc2 gene products were shown to act in synergy to repress the expression of Hoxb4 and -b8 rostral to the expression domain and also to maintain Hoxb8 expression within its expression domain. Very similar changes have been reported in the Rnf110-Bmi1 double mutant (12). In addition, since the derepression of Hoxb6 in Rnf110-Bmi1 double homozygotes has been shown to occur progressively between 8.5 and 9.5 dpc (3), Representative results show the association of the Phc2 protein with the second exonic region of Cdkn2a, using the adam34 coding region as a negative control.…”
Section: Vol 25 2005 Synergistic Actions Of Mouse Polyhomeotic Homosupporting
confidence: 77%
See 3 more Smart Citations
“…Therefore, Phc2 gene products were shown to act in synergy to repress the expression of Hoxb4 and -b8 rostral to the expression domain and also to maintain Hoxb8 expression within its expression domain. Very similar changes have been reported in the Rnf110-Bmi1 double mutant (12). In addition, since the derepression of Hoxb6 in Rnf110-Bmi1 double homozygotes has been shown to occur progressively between 8.5 and 9.5 dpc (3), Representative results show the association of the Phc2 protein with the second exonic region of Cdkn2a, using the adam34 coding region as a negative control.…”
Section: Vol 25 2005 Synergistic Actions Of Mouse Polyhomeotic Homosupporting
confidence: 77%
“…It is possible that these results tie in with the recent discovery that class II PcG complexes are associated with a positive function. Null mutations in the Rnf110 and Phc1 loci have been shown to decrease the transcription level of endogenous Hoxb1 and to severely impair the transcription from Hox-LacZ reporters and knockin loci (12). In addition, a positive action of PcG complexes could explain the fall in gene expression levels within Hoxb8 expression domains, which has been reported to be around 9.5 dpc in Phc2-Phc1 and Bmi1-Rnf110 and double mutants (3,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to their role in the epigenetic maintenance of transcriptional states of their target genes, PcG and trxG protein complexes probably regulate the transcription of their targets in Drosophila (Breiling et al, 2001;Saurin et al, 2001), as well as in early mouse embryos (de Graaff et al, 2003). A recent study (Milne et al, 2002) elegantly showed that the binding of SET domain methyl transferase activity to the proximal promoter of human HOXC8 in cultured fibroblasts was crucially required for transcription of the gene.…”
Section: (See Box 2)mentioning
confidence: 99%